Bedtime routines in Greek families: characteristics, barriers, and facilitators for establishing and maintaining optimal routines - Papadopoulou, Marina; Sandalidou, Maria; Kamarligkos, Ioannis; Kitsakis, Nikolaos; Milonaki, Maria-Aggeliki; Zografou, Frideriki; Kitsaras, George (Frontiers in Sleep, 2024)
Background; Bedtime routines are amongst the most common, recurrent family activities with close associations for child health, development and wellbeing especially sleep. Despite the importance of bedtime routines, no previous study has examined them within the context of a Greek family. Method; A mixed methods, stepped approach was used in this study. A cross-sectional study examined the prevalence and characteristics of bedtime routines (PRE) in families with young children and explored associations with parental mood (POMS) and child's sleep (CSHQ). A qualitative study using the Theoretical Domains Framework (TDF) examined barriers and facilitators for achieving optimal routines. Results; Total of 54 parents with a mean age of 35.9 (SD=5.95) completed the crosssectional study while 20 parents participated in the interviews. There were strong positive correlations between total scores on the POMS and total scores on the CSHQ r=.482, p<.001 and strong negative correlation between total scores on the POMS and total scores on the PRE, r=-.308, p=.023. In terms of barriers and facilitators, social desirability, social comparison, environmental factors and resistance from children were amongst the most common barriers to establishing a good bedtime routine. Conclusion; Bedtime routines are highly prevalent in Greek families with the quality of those routines varying between households. Addressing common barriers in achieving better bedtime routines could help families benefit in the short and long-term.